The neutralizing effect of heparin on blood-derived antimicrobial compounds: impact on antibacterial activity and inflammatory response - Cont, Denisa; Harm, Stephan; Schildböck, Claudia; Kolm, Claudia; Kirschner, Alexander K. T.; Farnleitner, Andreas H.; Pilecky, Matthias; Zottl, Jennifer; Hartmann, Jens; Weber, Viktoria (Frontiers in Immunology, 2024)
Acting through a combination of direct and indirect pathogen clearance mechanisms, blood-derived antimicrobial compounds (AMCs) play a pivotal role in innate immunity, safeguarding the host against invading microorganisms. Besides their antimicrobial activity, some AMCs can neutralize endotoxins, preventing their interaction with immune cells and avoiding an excessive inflammatory response. In this study, we aimed to investigate the influence of unfractionated heparin, a polyanionic drug clinically used as anticoagulant, on the endotoxin-neutralizing and antibacterial activity of blood-derived AMCs.Serum samples from healthy donors were pre-incubated with increasing concentrations of heparin for different time periods and tested against pathogenic bacteria (Acinetobacter baumannii, Enterococcus faecium, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus) and endotoxins from E. coli, K. pneumoniae, and P. aeruginosa. Heparin dose-dependently decreased the activity of blood-derived AMCs. Consequently, pre-incubation with heparin led to increased activity of LPS and higher values of the pro-inflammatory cytokines tumor necrosis factor α (TNF-α) and interleukin 6 (IL-6). Accordingly, higher concentrations of A. baumannii, E. coli, K. pneumoniae, and P. aeruginosa were observed as well. These findings underscore the neutralizing effect of unfractionated heparin on blood-derived AMCs in vitro and may lead to alternative affinity techniques for isolating and characterizing novel AMCs with the potential for clinical translation.